2015
DOI: 10.1177/0269216315613904
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Problem Severity Score: Reliability and acceptability in a national study

Abstract: The Palliative Care Problem Severity Score is an acceptable measure, with moderate reliability across three domains. Variability in inter-rater reliability across sites and participant feedback indicate that ongoing education is required to ensure that clinicians understand the purpose of the tool and each of its domains. Raters familiar with the patient they were assessing found it easier to assign problem severity, but this did not improve inter-rater reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 14 publications
0
39
0
3
Order By: Relevance
“…45 Thus, by promoting team consensus and communication, the instrument fulfills an important role. In our analysis of other tools, we found that PCPSS 46 does not include an ethical or death-related domain, nor does it differentiate between the spiritual and psychological/emotional domains that PC-NAT does; 47,48 NAT-PD-C 49 is exclusively used for cancer cases and NAT-PD-HF 50 for advanced heart disease; CSNAT 51 is specifically aimed at caretakers; NA-ACP 52 and NEST13 53 test patient response; and, lastly, IDCPAL is focused more on management than clinical practice. 54 None of the aforementioned tools specifically examines resources and strengths.…”
Section: Discussionmentioning
confidence: 91%
“…45 Thus, by promoting team consensus and communication, the instrument fulfills an important role. In our analysis of other tools, we found that PCPSS 46 does not include an ethical or death-related domain, nor does it differentiate between the spiritual and psychological/emotional domains that PC-NAT does; 47,48 NAT-PD-C 49 is exclusively used for cancer cases and NAT-PD-HF 50 for advanced heart disease; CSNAT 51 is specifically aimed at caretakers; NA-ACP 52 and NEST13 53 test patient response; and, lastly, IDCPAL is focused more on management than clinical practice. 54 None of the aforementioned tools specifically examines resources and strengths.…”
Section: Discussionmentioning
confidence: 91%
“…However, for other PCOC tools, a proxy rating is highly valid. 42 Finally, the SAS does not provide assessments of other problems that might be bothersome at the end of life, including anxiety or depression.…”
Section: Limitations Of the Workmentioning
confidence: 99%
“…Zu Beginn der Betreuung wird ein Aufnahmebogen erstellt, der seit 2012 folgendes enthält: Alter, Geschlecht, Diagnose, den Australia Modified Karnofsky Performance Score (AKPS), welcher das Ausmaß von Krankheitszeichen, der Hilfebedürftigkeit sowie der Bettlägerigkeit graduiert [9] sowie den in 4 (0-3) Kategorien (Schmerz, andere Symptome, psychologisch/spirituell, Angehörigenunterstützung), und nach je 4 Abstufungen (0 = fehlend, 1 = mild, 2 = moderat,3 = schwer) eingeteilten Palliative Care Problem Severity Score (PCPSS) [10] Durchführung und Ergebnisbericht basieren auf den Empfehlungen des STROBE-Statements [11], sowie der GPS-Leitlinien [12]. ges of patient characteristics as well as the contents of care within time are scarce.…”
Section: Materialien Und Datensätzeunclassified
“…1). 50,1 % waren weiblich, 49,9 % männlich.Entwicklung der Sorgepunkte für den SterbeprozessDer beim Aufnahmezeitpunkt verwendete PCPSS[10] stellt ein praxistaugliches, validiertes Raster dar, das die palliative Situation im Überblick erfasst. Zum Sterbezeitpunkt können nur selten Beschwerden oder psychische Probleme vom Patienten erfragt, der PCPSS also nicht mehr verwendet werden.…”
unclassified